THU0641-HPR ILLITERACY IS NOT AN OBSTACLE FOR ASSIMILATION OF A PATIENT EDUCATION SESSION ON METHOTREXATE SELF-INJECTION IN RA PATIENTS A PROSPECTIVE PILOT STUDY. (2nd June 2020) - Afilal, S.; Rkain, H.; Berchane, B.; Moulay Berkchi, J.; Fellous, S.; Fatima Zahrae, T.; Ilham, A.; Alami, N.; Latifa, T.; Hajjaj-Hassouni, N.; Allali, F.
Abstract : Background: Patient education for RA patients has been shown to improve adherence and self-management of this chronic disease. Objectives: To assess the impact of illiteracy on assimilation of a patient education session on methotrexate self-injection in RA patients. Methods: Prospective pilot study that included 27 consecutive patients (81.5% female, mean age 44.4 years, illiteracy rate 40.7%) with RA (median duration of progression of 4 years, mean delay in referral for specialist of 6 months, median duration of methotrexate use of 1 year). The patients benefited from an individual patient education session to learn how to self-inject with methotrexate subcutaneously. The patient education session was supervised by a nurse and a rheumatologist. A 10-question dichotomous questionnaire was then administered to patients to assess the level of uptake of messages passed during the patient education session. The prevalence of correct answers was compared between illiterate and non-illiterate patients. Results: The mean duration of patient education session is 13 min. Table I illustrates the results of the correct responses prevalence and the comparison of correct response rates between illiterate and non-illiterate patients. Conclusion: This study suggests that illiteracy does not affect the assimilation of information given during a patient education session. These preliminary results should encourage the development of patient education programs in our context where illiteracy rate is high. Disclosure of Interests: None declared